High prevalence of disability and HIV risk among low socioeconomic status urban adults, 17 U.S. cities - Doyle, Katherine E. (Disabil Health J, 2019)
BACKGROUND: In the United States, approximately 10% of adults 18–64 years are disabled. However, there is scarce literature on the associations between disability and HIV risk. OBJECTIVE: To assess disability prevalence and its associations to health and HIV risk factors among low socioeconomic status (SES) (≤high school education or ≤ poverty guidelines) urban adults. METHODS: We assessed disability prevalence from a cross-sectional sample of low SES urban heterosexually active adults at risk for HIV participating in the 2016 National HIV Behavioral Surveillance (NHBS) and calculated crude and adjusted prevalence ratios and 95% confidence intervals of disability for health and HIV risk behaviors. RESULTS: In the NHBS sample, 39.6% of participants reported any disability. Disability was associated with health care utilization and risk behaviors, even when adjusting for demographics. Participants with disabilities were more likely to have condomless sex with a casual partner and engage in exchange sex. CONCLUSIONS: Low SES urban heterosexually active adults reported high prevalence of disabilities and differences in health, health care utilization, and risk factors. Disability might contribute to sexual risk behaviors that increase the likelihood of HIV infection. Further investigations into the intersection of disability and HIV risk are needed, especially in poor communities often excluded from national assessments.